Sociodemographic factors which predict low private rabies vaccination coverage in dogs in Blantyre, Malawi. (2nd March 2019) - Mazeri, Stella; Gibson, Andrew D; de Clare Bronsvoort, Barend Mark; Handel, Ian G; Lohr, Fred; Bailey, Jordana Burdon; Mayer, Dagmar; Gamble, Luke; Mellanby, Richard J
Abstract : Although rabies kills approximately 60, 000 people globally every year, vaccination of over 70 per cent of the canine population has been shown to eliminate the disease in both dogs and human beings. In some rabies endemic countries, owners are able to vaccinate their dogs through private veterinary clinics. However, uptake of dog vaccinations through private veterinary clinics is often low in many rabies endemic countries. In this study, the authors examined the sociodemographic factors which predicted low private rabies vaccination coverage in Blantyre, Malawi. Data on 23, 205 dogs were recorded during a door‐to‐door rabies vaccination programme in 2016. A multivariable logistic regression model was built to identify factors associated with private rabies vaccination. Negative predictors of private vaccination included increasing poverty levels, higher housing densities, male dogs, pregnant or lactating dogs, and puppies and dogs allowed to roam. In contrast, neutered and healthy dogs had greater odds of being privately vaccinated. The present study demonstrated that low private rabies vaccination coverage can be accurately predicted by sociodemographic factors. This information may help inform public health interventions which deliver mass vaccination programmes in rabies endemic countries.